2004
DOI: 10.1095/biolreprod.102.014969
|View full text |Cite
|
Sign up to set email alerts
|

HOXC and HOXD Gene Expression in Human Endometrium: Lack of Redundancy with HOXA Paralogs1

Abstract: HOXA genes, essential regulators of differentiation in the embryo, are also essential for adult cyclic endometrial development and for endometrial receptivity. Mice deficient in Hoxa10 or Hoxa11 exhibit reduced fertility because of defects in implantation. We hypothesized that HOXC10, HOXC11, HOXD10, and HOXD11, paralogs of HOXA10 and HOXA11, might also be involved in endometrial development. Here, we showed that the expression of HOXC10, HOXC11, HOXD10, and HOXD11 was evident throughout the menstrual cycle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 43 publications
(64 reference statements)
4
40
0
Order By: Relevance
“…These genes show a consistent correlation between DNA methylation and gene expression which is altered in endometriosis, although their function in the endometrium remains largely unknown. HOXD10 has been implicated in endometrial stromal cell proliferation, and our pathway analysis comparison identified it as well, suggesting that all of the HOX clusters may show aberrant methylation in endometriosis [42].…”
Section: Discussionmentioning
confidence: 70%
“…These genes show a consistent correlation between DNA methylation and gene expression which is altered in endometriosis, although their function in the endometrium remains largely unknown. HOXD10 has been implicated in endometrial stromal cell proliferation, and our pathway analysis comparison identified it as well, suggesting that all of the HOX clusters may show aberrant methylation in endometriosis [42].…”
Section: Discussionmentioning
confidence: 70%
“…This observation indicates that HOXA11 transcription in the endometrium is not affected by embryonic stimuli and the expression of both these orthologs may not be strictly coregulated during the process of implantation. Indeed, no correlation has been found in expression profiles of HOX orthologs in human endometrium during different phases of menstrual cycle (Akbas & Taylor 2004), indicating a lack of redundancy and existence of independent regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, in vitro studies suggested that PGE2 and relaxin act via IL-11 to phosphorylate Stat3, which enhances P-induced decidualization in cultured human stromal cells (6). A decrease in genes from the HOX cluster such as hoxc10, hoxc11, hoxd10, and hoxd11 during the implantation window, which was also observed, suggests that these transcriptional repressors may interfere with the preparation of the endometrium for implantation (7).…”
mentioning
confidence: 86%